Lack of neuroprotection after systemic administration of the soluble TNF inhibitor XPro1595 in an rAAV6-α-Syn + PFFs-induced rat model for Parkinson’s disease - Fredlund, Filip (2025)
Previous research has shown that international donors can significantly influence national and international environmental governance. However, their influence at the regional level has not yet been sufficiently explored. This study aims to examine the influence of international donors on regional environmental governance agreements, taking the Amazon Cooperation Treaty (ACT) as a case study. Using a documentary analysis covering four decades, reviews of academic literature and media articles, and interviews with key informants, this study traces the influence of donors through three distinct stages: protectionism, formalisation and policy customisation. In the first stage, the limited influence of international donors did not translate into significant changes in the initially low degree of formalisation of the agreement. In the second stage, the moderate to high influence of international donors led member states to enhance the degree of formalisation of the ACT and to adopt for the first time a weak forest-related policy in the search to increase its capacities to attract and manage external funds. In the third stage, the still high influence of international donors increased the strength of the newly adopted forest-focused policy of the ACT to moderate. We conclude that international donors can influence regional environmental governance arrangements by increasing their degree of formalisation and the strength of their (forest) policies, and by customising these policies to their own interests rather than those of the members of the arrangements.